Clopidogrel pretreatment of patients with ST-elevation myocardial infarction does not affect platelet reactivity after subsequent prasugrel-loading: Platelet reactivity in an observational study. (November 2013) - Nührenberg, Thomas G.; Trenk, Dietmar; Leggewie, Stefan; Ristau, Inga; Amann, Michael; Stratz, Christian; Hochholzer, Willibald; Valina, Christian M.; Neumann, Franz-Josef
<x xml:space="preserve">Abstract</x> Current guidelines recommend prasugrel or ticagrelor for patients undergoing percutaneous coronary intervention (PCI) in ST-elevation myocardial infarction (STEMI). Whereas available data support ticagrelor independent of pretreatment with clopidogrel, corresponding data for prasugrel are missing. Here, we investigated platelet reactivity after loading with prasugrel in clopidogrel-naïve vs. clopidogrel-pretreated patients. Forty-seven consecutive patients with STEMI referred for primary PCI were enrolled. Use of GPIIb/IIIa inhibitors and known contraindications to prasugrel served as exclusion criteria. A total of 31 patients were already treated with a loading dose of clopidogrel 600 mg by the emergency medical system before admission, while 16 patients were P2Y12 antagonist naïve. All patients received a loading dose of prasugrel 60 mg immediately before PCI. Adenosine diphosphate (ADP) induced platelet reactivity was determined by VerifyNow™ P2Y12 assay, by light transmission aggregometry (LTA) and by multiple electrode impedance aggregometry (MEIA; Multiplate™ analyser). No differences in platelet reactivity were observed at day 1 after PCI between the bolus-on-bolus treatment regimen and single prasugrel loading. Platelet reactivity was profoundly decreased to 10 [8–31] platelet reactivity unit (PRU; median [interquartile range]) in patients on clopidogrel + prasugrel vs. 9 [6–60] PRU in patients on prasugrel only (p = 0.916). Consistent results were obtained by LTA and MEIA. The proportion of patients reaching a MEIA associated with increased risk bleeding (<188 AU*min) was also similar between the two study groups. The level of platelet reactivity at day 1 after the 60 mg loading dose of prasugrel was independent of pretreatment with clopidogrel. Our results do not support withholding prasugrel in patients pretreated with clopidogrel who undergo PCI for STEMI.